ANALISIS PENGARUH RETURN ON ASSETS (ROA), EARNING PER SHARE (EPS), DAN DEBT TO EQUITY RATIO (DER) TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan yang Tercantum dalam Indeks LQ45 BEI Periode 2013-2016) - Alif Wahyu Wicaksana; Abdul Qodir Djaelani; Muhammad Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT"Analysis Of Effect Of Return On Assets (Roa), Earning Per Share (Eps),And Debt To Equity Ratio (Der) On Company Value”(empirical study on companies listed in LQ45 index IDX period 2013-2016) The purpose of this research is to know and analyze how influence on partial and simultaneous Return On Assets (ROA), Earning Per Share (EPS), dan Debt ToEquity Ratio (DER) to firm value on companies listed on LQ45 BEI period 2013- 2016. Type of this research is quantitative research by using secondary data of company financial report on LQ45 index. The sample are having 23 companies from 64 companies on the index LQ 45. Sampling technique using purposive sampling. The result of this research is that Return On Assets (ROA) have a significant and positive influence on firm value, Earning Per Share (EPS) has no significant effect and positive influence on firm value, Debt to Equity Ratio (DER) the value of the company. Simultaneously Return On Assets (ROA), Earning Per Share (EPS) and Debt to Equity Ratio (DER) have a significant and positive effect on firm value.Keyword : Return On Assets (ROA), Earning Per Share (EPS), dan Debt ToEquity Ratio (DER), and firm value